In vitro comparison of naturally bioactive plant extracts, essential oils, and marine algae targeting different modes of action for mitigation of enteric methane emissions in ruminants - Hodge, Ian; Quille, Patrick; Ayyachamy, Manimaran; O'Connell, Shane (Frontiers in Animal Science, 2025)
Feed additives to reduce enteric methane (CH4) emissions from ruminants are gaining attention to help curb agriculture’s 24% share of global CH4 emissions. Several mechanisms of action of feed additives for mitigating rumen methanogenesis have been identified from ongoing research, however, there is still a need to determine the most effective method and explore potential synergies between these different approaches. This study evaluates the CH4 mitigation potential of nine natural feed additives, focusing on their mode of action in reducing CH4 emissions during in vitro fermentation. The natural feed additives assessed include garlic oil (GO), garlic powder (GP), allicin (ALL), yucca schidigera plant extract (Yucca), and an essential oil blend (EO), all functioning as rumen microbiome modifiers. Calcareous marine algae rumen buffer (CMA) and its magnesium oxide-fortified form (CMA.MgO) acted as hydrogen sinks, while Asparagopsis taxiformis (cultured and ocean forms) inhibited the central enzyme involved in methane metabolism. Total gas, CH4, and volatile fatty acid (VFA) outputs were recorded after in vitro batch fermentations simulating rumen 24 h metabolic events. The CMA.MgO rumen buffer displayed significant reductions (P=0.02) in both CH4 emissions relative to the control (Rel % CH4; 40.1%) and total gas production relative to the control (Rel % Total gas; 22.9%). The greatest synergistic effect on gas emissions was achieved by combining GP with the CMA buffer treatment, leading to significant reductions (P<0.05) in Rel % Total gas by 37% and Rel % CH4 by 64.5%. Additionally, sole supplementation of CMA.MgO, GO, and Yucca demonstrated improved rumen productivity by increasing total VFAs by 39.8%, 24.4%, and 22.6% compared to the control result, respectively. Feed additives altering rumen microbial populations by reducing methanogens and promoting VFA production increase readily available energy for the animal while reducing CH4 generation significantly. Semi-continuous rumen culture fermentations or in vivo studies can confirm the long-term stability of synergistic antimethanogenic mechanisms, potentially optimizing CH4 inhibitors like A. taxi and EO for commercial use.